Carbothermal synthesis of high-aspect-ratio AlN whiskers using graphite felt as carbon source. Issue 7 (1st April 2022) - Hao, Xu; Wan, Shiqin; Kang, Weiwei; Zhao, Jialiang; Han, Sumei; Peng, Dongyao; Yang, Pan; Wang, Qi
Abstract: In this study, aluminum nitride (AlN) whiskers were successfully synthesized via carbothermal reduction nitridation (CRN) method. Graphite felt was used as carbon source and growth substrate, while no any catalyst was introduced. It is found from TEM and SEM analysis that the AlN whiskers grew along [001] direction, presenting uniform morphology and smooth surface with a length of up to microns. The high purity and high crystallinity of the whiskers were confirmed by XRD, XPS and Raman scattering spectrum. In addition, the influence of reaction temperature was systematically investigated, and it was indicated that excessively low or high temperature could both lead to the reduced whisker yield. On basis of the working results, the underlying gas-solid (VS) growth mechanism of AlN whiskers was significantly proposed.